A 2nd‐Order Noise Shaping SAR ADC Realizing NTF Zero‐Pole Optimization Based on IIR‐FIR Filter. Issue 1 (1st January 2022) - ZHANG, Yanbo; LIU, Shubin; LIANG, Yuhua; ZHU, Zhangming
Abstract : This paper reports a successive approximation register (SAR) analog‐to‐digital converters (ADCs) with the 2nd‐order and optimized noise shaping (NS) scheme. Based on the feed‐forward structure, both noise transfer function (NTF) zero and pole optimization have been achieved simultaneously utilizing a cascaded IIR‐FIR (infinite impulse response and finite impulse response) filter. The analysis shows that the proposed structure provides a better NS efficiency than prior arts. The efficiency of the proposed NS scheme and the ADC performance are verified by simulation achieving a 14.2 effective number of bits with an 8‐bit SAR ADC architecture at an over sampling rate of 8 sampled at 100 MS/s. Taking advantage of the NTF zero‐pole optimization, a low resolution SAR ADC is allowed under the same quantization noise budget in this structure.